Thailand Manufacturing Firm Productivity Report - World Bank (World Bank, Bangkok, 2020)
Thailand is an enduring development success story. Between the late 1960s and mid-1990s, strong and sustained economic growth propelled the country from low-income to upper-middle-income status. To achieve high-income status by 2037, the authorities will need to draw on the experiences of other upper-middle-income countries that have successfully completed the transition, as well as those that continue to struggle. The Coronavirus (COVID-19) outbreak has severely impacted growth in Thailand, with the economy expected to contract in 2020 amid heightened uncertainty surrounding the path of the pandemic. This report focuses on the manufacturing sector builds on a framework that emphasizes the microeconomic and macroeconomic linkages of the sources of productivity growth. In line with this framework, Chapter 1 begins with an overview of Thailand’s productivity dynamics at the macroeconomic level and identifies the causes of its slowing GDP growth rate.7 Chapter 2 analyzes the characteristics of Thai manufacturing firms and sub-sector productivity dynamics, revealing the drivers of firm productivity and distinguishing the relative contributions of within-firm effects, between-firm effects, and market dynamism. Chapter 3 evaluates the impact of competition on firm productivity by comparing market entry and exit indicators with price markups. Chapter 4 concludes with a set of policy recommendations designed to boost firm productivity in Thailand’s manufacturing sector.